Mechanical properties of orthodontic wires on ceramic brackets associated with low friction ligatures - Fernando KOIKE; Hiroshi MARUO; Rogério LACERDA-SANTOS; Matheus Melo PITHON; Orlando Motohiro TANAKA (Universidade Estadual Paulista, 2017)
Abstract Introduction Few studies investigated the mechanical properties of orthodontic wires on ceramic brackets associated the ligatures. Objective This study aimed to compare the load-deflection of orthodontic wires with round section of 0.016" made of stainless steel (SS), nickel-titanium (NiTi) and glass fiber-reinforced polymer composite (GFRPC). Material and method Sixty specimens obtained from 10 sectioned pre-contoured arches (TP Orthodontics), were divided into 3 groups of 20 according to each type of material (1 esthetic-type wire and 2 not esthetic) and length of 50 mm. The methodology consisted of a 3-point bending test using esthetic ceramic brackets (INVU, TP Orthodontics, Edgewise, 0.022"x 0.025") as points of support. The tensile tests were performed on a mechanical test machine, at a speed of 10 mm/min, deflection of 1 mm, 2 mm and 3 mm. Friedman's Non Parametric Multiple comparisons test was used (P<0.05). Result The nickel-titanium wire presented smaller load/ deflection compared with stainless steel. GFRPC wires had lower strength values among all groups evaluated (P<.05). The steel wire showed permanent deformation after 3 mm deflection, NiTi wire demonstrated memory effect and the esthetic type had fractures with loss of strength. Conclusion It can be concluded that steel wires have high strength values, requiring the incorporation of loops and folds to reduce the load / deflection. NiTi and GFRPC wires produced low levels of force, however the esthetic wire was shown to fracture and break.